2016
DOI: 10.21817/ijet/2016/v8i5/160805061
|View full text |Cite
|
Sign up to set email alerts
|

A methodology based on GIS for 3D Slope Stability Analysis

Abstract: Abstract-In this paper, we present an analysis of slope stability using Geographic Information Systems (GIS). The methodology is based on the calculation of the safety factor in 2D and 3D using GIS. Hovland's Method in 3D and 2D have been used in the stability analysis of the slope located at the 34 kilometer point (KP.34) on the highway in the North of Morocco connecting Tangier to Ksar Sghir. Isohypse and the digital elevation model (DEM) of the studied site have been built from topographical surveys. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…• The horizontal displacement of the soil was close to the measured in situ. Also, the measured displacements revealed that the method of reinforcement by piles used in some areas of the study effectively stabilizes landslides, and not others [44].…”
Section: Resultsmentioning
confidence: 90%
“…• The horizontal displacement of the soil was close to the measured in situ. Also, the measured displacements revealed that the method of reinforcement by piles used in some areas of the study effectively stabilizes landslides, and not others [44].…”
Section: Resultsmentioning
confidence: 90%
“…Over time, the literature has been enriched with numerous methods for stability analyses, developed by academics and researchers in the field, among which we mention: methods based on the limit equilibrium concept [1][2][3][4][5][7][8][9][10]; methods based on finite element/difference method [3,4,[7][8][9][10]12,13,49] (which is a modern and accurate one, able to be applied to complex structures); methods based on 3D analyses [29,40,41,[50][51][52][53][54] (for slopes with complex geometries, partially loaded, with variable structure, having a well-defined failure mechanism and assuming the addition of the third dimension in 2D models); probabilistic methods [55][56][57][58] (implies probabilistic analysis and processing of the physical-mechanical properties of the rocks and probabilistic computation by analytical or numerical methods); methods using Fuzzy logic [59][60][61][62][63] Considering the positive influence that lignite can exert on the stability reserve, due to its superior resistance characteristics compared to the surrounding (waste) rocks, Table 5 presents a situation regarding the position occupied by the lignite layers in relation to the slopes (existing, as of May 2023, and designed at the end of 2023). Next, in the model made with the help of the specialized software Slide (Figure 10), the values of the physical and mechanical characterist...…”
Section: Results Of the Stability Analysesmentioning
confidence: 99%
“…A possible continuation of this study envisages the use of software that performs stability analysis based on finite elements or the finite differences method [73][74][75][76][77], 3D modeling [78][79][80][81][82] and probabilistic approaches [83][84][85][86].…”
Section: Final Conclusionmentioning
confidence: 99%